Deltacoronavirus HKU11, HKU13, PDCoV (HKU15) and HKU17 spike pseudoviruses enter avian DF-1 cells via clathrin-mediated endocytosis in a Rab5-, Rab7- and pH-dependent manner - Qi-Zhang Liang; Chun-Miao Ji; Bin Wang; Wei Chen; Feng Cong; Yu Huang; Yao-Wei Huang (Veterinary Research)
Abstract Porcine deltacoronavirus (PDCoV), also known as HKU15, is a swine enteropathogenic virus that is believed to have originated in birds. PDCoV belongs to the genus Deltacoronavirus (DCoV), the members of which have mostly been identified in diverse avian species. We recently reported that chicken or porcine aminopeptidase N (APN), the major cellular receptor for PDCoV, can mediate cellular entry via three pseudotyped retroviruses displaying spike proteins from three avian DCoVs (HKU11, HKU13, and HKU17). In the present work, to better understand how avian-origin CoVs may be transmitted to pigs, we investigated the unknown DCoV entry pathway in avian cells. We show that clathrin-mediated endocytosis is involved in the entry of these DCoV pseudoviruses into chicken-origin DF-1 cells. Pseudovirus entry was suppressed by means of pharmacological inhibitors, dominant-negative mutants, and siRNAs targeting various cellular proteins and signalling molecules, suggesting that PDCoV and avian DCoV pseudovirus entry into DF-1 cells depends on clathrin, dynamin-2, cathepsins and a low-pH environment but is independent of caveolae and macropinocytosis. Furthermore, we found that DCoV pseudovirus entry was linked to Rab5- and Rab7-dependent pathways. This is the first report demonstrating that these DCoVs utilize clathrin-mediated endocytosis pathways to enter avian-origin cells, providing new insights into interspecies transmission of DCoVs.